Historical Examination and Reflection on the Reasons for the “Curtain Call” of Church Universities in the Early 1950s: The Case of Yenching University - ZHANG Jianmei (Journal of Research for Christianity in China (JRCC), 2025)
Church-affiliated universities made indelible contributions to China’s modern higher education history, yet collectively withdrew from the Chinese academic landscape in the early 1950s. As one of the most influential such institutions, Yenching University’s reasons for and process of “exit” to some extent epitomized the broader withdrawal of church-affiliated universities from the historical stage. This paper uses Yenching University as a case study to conduct a historical examination of the “exit” of missionary universities in the early 1950s. After the founding of the People’s Republic of China, Yenching University made corresponding adjustments, whether voluntarily or involuntarily, yet it could not escape the fate of being abolished. The decisive factor in Yanjing University’s closure was its very nature as a missionary institution. Its educational model also failed to meet the new nation’s demand for mass production of specialized technical talent. Furthermore, the developmental requirements of the new Chinese higher education system, coupled with Yanjing’s own challenges in funding sources and student recruitment, significantly influenced its ultimate fate. The “curtain call” of Yanjing University and other missionary universities undoubtedly represented a significant loss for China’s higher education sector. It substantially impacted institutional autonomy, teaching quality, and international exchange. For the missionary universities themselves, it meant facing the ultimate outcome of dissolution. Contemporary Chinese higher education should engage in profound reflection on the “curtain call” of Yenching University in the 1950s. It must earnestly explore the intrinsic laws governing higher education development, strive to create a diverse, open, and free environment for its advancement, and propel Chinese higher education toward a qualitative leap forward.